Performance evaluation of 4D-8PSK-TCM for LEO satellite - Kim, Song; Cho, Jun Woo; Kim, Kyeong Rok; Kim, Jae Hyun (Proceedings - 2019 IEEE VTS Asia Pacific Wireless Communications Symposium, APWCS 2019, 2019)
High-speed transmission technology is required to provide various services through Low Earth Orbit (LEO) satellites. The Consultative Committee for Space Data System (CCSDS) recommends the four Dimension 8-ary Phase Shift Keying Trellis Coded Modulation (4D-8PSK-TCM) system for high-speed transmission of large amounts of data in the X-band. In this paper, we build the 4D-8PSK-TCM system with transmission efficiency of 2.0 bits/channel-symbol using MATLAB Simulink. The performance is evaluated in terms of the Bit Error Rate (BER) and throughput over time through network-level simulator using Riverbed Modeler. The results show that there is no difference between the throughput of 4D-8PSK-TCM and that of other schemes in the X-band regardless of the simulation time. However, the 4D-8PSK-TCM has an advantage of the BER.
Keywords: 4D-8PSK-TCM; Consultative committee for space data systems; LEO satellite; Low earth orbit satellites; Network level; Rain fading; Transmission efficiency; Trellis coded modulation; 4D-8PSK-TCM; LEO Satellite; Modulator; Network-level Simulator; Rain-fading